Looking Back at MIA. Issue 1 (February 2014) - Goot, Murray; Tiffen, Rodney
Murray Goot and Rodney Tiffen were among the six editors appointed to manage MIA after Henry Mayer's death in 1991. In this entry from A Companion to the Australian Media, they provide an overview of the journal's 38-year history.